PENGARUH FAKTOR EKSTERNAL TERHADAP AKTIFITAS FISIK PASIEN HIPERTENSI - Rischar Beny Riswanto; Nursalam Nursalam; Abu Bakar (Universitas Muhammadiyah Kudus, 2021)
AbstractPatients with hypertension were mostly found to have low levels of healthy lifestyle compliance. Patients with hypertension are required to get health counseling in order to adhere to a healthy lifestyle in order to control blood pressure and prevent complications. The purpose of this study was to analyze the influence of external factors (affordability of health services, support of health workers and family support) on the physical activity of hypertensive patients. The design of the research is descriptive correlational with a cross sectional approach. The large sample sampled 145 hypertensive patients. Data collection is done using questionnaires. Data analysis using bivariate tests obtained results of health service affordability (p=0.009), health care worker support (p=0.021) and family support (p=0.012) to the physical activity of hypertensive patients. The results of this study can help the puskesmas in identifying lifestyle compliance of hypertensive patients and help patients in understanding treatment regimens to improve lifestyle compliance.